The tech that comes next : how changemakers, philanthropists, and technologists can build an equitable world - Ward, Amy Sample, 1982-; Bruce, Afua (John Wiley & Sons, Inc., 2022)
"Data, technology, and AI are considered by most to be effective tools in helping to level the playing field for all, whether you are talking about businesses, nonprofits, or even communities. Yet in truth, technology and equity are not eventual partners. Technology, data decision making, and investment needs to be centered in equity and community needs if a better world is to come. Active participation by folks from all sides of the sector is necessary for making real the changes we present. This includes social impact organizations changing the way they use technology and data, technology creators changing who is involved and how they make technology, and investors and funders redirecting assets to those most connected to the needs. A different world is possible and we can start building it today. After reading this book, regardless of whether the reader is a nonprofit staff person or executive, a tech startup founder or a developer, a VC investor or a foundation program officer, or even a community member thinking about how things could be different, readers will know what next steps they may want to take and how to begin upon implementing changes within their organizations to achieve data equity. Tech Equity will identify a number of areas where improvements within organizations is vital and will offer forth examples of how to get there. There will be many examples of what data equity can look like in all kinds of situations (tech development, investment, funding, community application, and more) to bring a focus on equity in technology into regular conversation, build commitments, and make real progress"--